(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Personal hygiene is important for after cesarean patients because personal hygiene will affect one’s health and psychological well-being. Patients with after cesarean wounds should be given immediate wound care by cleaning to prevent infection during the wound care. This will affect the wound healing process in cesarean surgery patients. This study aims to determine the relationship between personal hygiene and healing of after cesarean wounds in the NTB General Hospital. An accidental sampling technique of 52 patients with after cesarean section who experienced personal hygiene during wound care in the NTB General Hospital was used in this study using a prospective cohort study design. By using data analysis based on the chi square test, the results showed that personal hygiene in after cesarean patients was mostly good category of 40 respondents (76.9%), cesarean section wound healing in after cesarean patients most of the categories were cured as much as 46 respondents (88.5%) and obtained a p-value of 0.002 <0.05. The results of the study confirmed the relationship between personal hygiene and healing of after cesarean wounds in the NTB General Hospital. This study recommends that nurses and other health teams develop theories and guidelines for the implementation of personal hygiene that are more effective and efficient in order to reduce infection after cesarean section.